Role of adenosine deaminase in monitoring tubercular pleural effusion - Hazarika, Basanta; Sharma, Suresh; Kumar, Ritesh; Sarma, Jogesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis is a common cause of pleural effusion especially in countries like India. ADA (adenosine deaminase) is predominantly an enzyme, that catalyses the conversion of adenosine to ionosine. Usually patients with tuberculous pleural effusion have ADA level >40 U/L. Methods: This is a prospective, observational study conducted in Department of Pulmonary Medicine, Gauhati Medical College and Hospital, Guwahati from September 2016 to September 2017. 45 patients with pleural fluid ADA levels >40 U/L were selected with diagnosis of tubercular pleural effusion. Pleural fluid was analysed for cytological, biochemical and microbiological parameters along with ADA and malignant cell cytology. Anti-tubercular treatment (ATT) was started and pleural fluid ADA level were repeated after 15 days of ATT. Results: Pleural fluid ADA levels before the start of ATT intake and after 15 days of ATT intake were statistically analysed. Among 45 patients, 38 were male and 7 females. Mean age of the patients was 45.42±16.43 years. Mean pleural fluid ADA level before starting ATT was 64.49±31.78 U/L. After 15 days of ATT intake mean pleural fluid ADA level was 36.11±10.42 U/L, p value was statistically significant (p<0.05). Conclusions: Pleural fluid ADA significantly decreased after 15days of initiation of anti-tubercular treatment. Pleural fluid ADA can be a useful tool as a follow up biomarker in cases of tubercular pleural effusion.